PENGUKURAN KINERJA BISNIS MELALUI PENDEKATAN BALANCED SCORECARD DAN ANALYTICAL HIERARCHY PROCESS (AHP) - Sumani Sumani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2016)
The aim of this study is Analyzing the business performance using balanced scorecard approach and Analytical Hierarchy Process (AHP). The population in this study were all employees and members of BMT-UGT Sidogiri. The sampling technique was Stratified Random Sampling for employees and convenience random sampling for BMT-UGT members Sidogiri. level positions (positions) of employees at BMT-UGT Sidogiri be the foundation of a random sample and tiered. The research sample used in this study were 42 employees and 212 members of BMT-UGT Sidogiri. The results showed: (1). balanced scorecard approach, showed the financial perspective (BMT-UGT Sidogiri conditions were good); perspective of satisfaction (satisfied with the services Sidogiri BMT-UGT); internal business perspective (increasing the number of business units); learning and growth perspective (employee productivity has increased); (2). The analysis perspective Balanced Scorecard using AHP Analysis of the individual perspective Balanced Scorecard by using AHP shows that the perspective is considered the most influential on the performance of the company is customer perspective that has the highest weight value, while the factor most considered to have the highest influence on the customer's perspective is the growing number of members. In other hand, internal business perspective has lowest value as a result of AHP analysis